Pendidikan Perencanaan Menjelang Era Asia-Pasifik: Perlunya Fleksibilitas Pendidikan - Pradono, . (Center for Research and Community Services ITB, 1996)
Globalization in economy has resulted in economic interdependency on a global scale. Economic activities have experienced tertiary proc ess, or activities characterized by the domination of service sector activities. Eventhough this phenomenon is more intensive in developed countries, its implications, nonetheless, will affect the developing countries. At a certain level developing countries will play and experience this new pattern. Developing countries should seize this momentum rightly . Human resources preparation through education is very essential in utilizing this momentum. Planning education is one important area in responding to the changing world. Some adjustments with new rethoric in education world is needed.